Reconstruction of the bottom of the sulcus after surgical excision of reactional inflammatory fibrous hyperplasia: a case report (Research, Society and Development, 2023)
With the increase in population life expectancy, the search for prosthetic rehabilitation has become routine in dental offices. However, the use of prosthetic devices can contribute to the formation of lesions in the oral cavity, especially when they present maladaptation. Inflammatory Fibrous Hyperplasia (IHH) is a reactive lesion of the Fibrous Connective Tissue related to chronic local trauma of low intensity, commonly linked to the use of poorly adapted prostheses. This study aimed to report the case of a 52-year-old patient and her multidisciplinary treatment, who presented to the clinical examination, a lower prosthesis with maladaptation, being found below this, the presence of an irregular, sessile hyperplastic nodule, firm on palpation, with 3cm in diameter, in the region of the sulcus fundus and right inferior alveolar gingiva. Based on the history and characteristics presented by the lesion, Reactional Inflammatory Fibrous Hyperplasia was established as a probable diagnosis. Thus, in order to obtain diagnostic confirmation and appropriate treatment, surgical excision of the lesion was performed, with subsequent reconstruction of the affected sulcus fundus region, and thus sent for histopathological analysis. The surgical removal proved to be adequate, with an excellent postoperative healing, thus enabling the manufacture of a new prosthetic device. In addition, the biopsy results were compatible with the histological characteristics presented in the literature regarding HFI, with confirmation of the final diagnosis. Finally, it is noted that the identification and early diagnosis of Inflammatory Fibrous Hyperplasia are of paramount importance, since they help in obtaining a good prognosis.